Penerapan Hygiene dan Sanitasi Kitchen di Hotel X Samarinda (Hotel Berbintang 4) - Naila Faradila; Tauhid Hira; Dinda Maharani (Jurnal Pariwisata Bisnis Digital dan Manajemen, 2025)
Food safety assurance is a must for developing the food processing industry in order to have good quality products, safe and suitable for consumption, very competitive economically, and according to consumer tastes, in addition one of the hotel's income is obtained from restaurants that provide food and drinks. The existence of restaurants is one of the hotel's efforts to improve the quality of service for consumers. The kitchen is one of the important aspects that must be considered to ensure the quality of a restaurant. One way to get quality products that needs to be considered is hygiene and sanitation in the kitchen. The purpose of this study is to find out whether Hotel X, one of the 4-star hotels (****) in Samarinda has implemented SOPs regarding existing hygiene and sanitation. This study is a descriptive study with observational data collection techniques for 6 months from January to June 2025 through the table of hygiene and sanitation procedures that apply in the hotel. The result is that there are still procedures that have not been implemented in the selection of food ingredients, namely insect-free, shelves are labeled for each type of ingredient and their placement is still less than 2 inches from the wall and labels to identify the depositor then in food processing it is left open which will trigger contamination and there are still equipment that is not in good and clean condition, even though in serving food all have been implemented. Food contaminated with bacteria can cause food poisoning whose symptoms can be mild to fatal and directly affect the quality, safety, and freshness of food products which in turn shape the hotel's reputation and guest trust.